Measurement of the production of neighbouring jets in lead-lead collisions at √sNN=2.76 TeV with the ATLAS detector - Santos, S. P. Amor dos (2015)
This Letter presents measurements of correlated production of nearby jets in Pb+Pb collisions at √sNN=2.76 TeV using the ATLAS detector at the Large Hadron Collider. The measurement was performed using 0.14 nb-1 of data recorded in 2011. The production of correlated jet pairs was quantified using the rate, RδR, of "neighbouring" jets that accompany "test" jets within a given range of angular distance, δR, in the pseudorapidity-azimuthal angle plane. The jets were measured in the ATLAS calorimeter and were reconstructed using the anti-kt algorithm with radius parameters d=0.2, 0.3, and 0.4. RδR was measured in different Pb+Pb collision centrality bins, characterized by the total transverse energy measured in the forward calorimeters. A centrality dependence of RδR is observed for all three jet radii with RδR found to be lower in central collisions than in peripheral collisions. The ratios formed by the RδR values in different centrality bins and the values in the 40-80% centrality bin are presented.